LncRNA SNAI3-AS1 promotes PEG10-mediated proliferation and metastasis via decoying of miR-27a-3p and miR-34a-5p in hepatocellular carcinoma - Li, Yarui (Cell Death Dis, 2020)
During recent years, long noncoding RNAs (lncRNAs) have received focal attention due to their important function in cancer regulation. Though the relation between lncRNA SNAI3-AS1 and the development of hepatocellular carcinoma (HCC) has been described in our previous study, the role and the exact mechanism of SNAI3-AS1 are still unclear. In this study, qRT-PCR analysis revealed that the expression of SNAI3-AS1 was elevated and was correlated with the levels of PEG10 in HCC tissues. Through functional experiments, we determined that knockdown of SNAI3-AS1 and PEG10 inhibited the proliferation and metastasis, whereas overexpression of SNAI3-AS1 and PEG10 promoted the proliferation and metastasis of HCC cells. In addition, rescue experiments confirmed that upregulation of PEG10 partially restored cell function inhibition induced by SNAI3-AS1 knockdown. Therefore, we hypothesized that PEG10 may be regulated by SNAI3-AS1, which in turn mediates the malignant biological processes of HCC cells regulated by PEG10. Further bioinformatics analysis and mechanistic experiments showed that SNAI3-AS1 functions as a competing endogenous RNA (ceRNA) to activate PEG10 by acting as a sponge for miR-27-3p and miR-34a-5p. In summary, our study revealed that SNAI3-AS1 is a tumor regulator of PEG10 in the progression of HCC, and may contribute to the improvement of HCC diagnosis and therapy.